2020
DOI: 10.21307/jofnem-2020-094
|View full text |Cite
|
Sign up to set email alerts
|

Yellow and purple nutsedge and coffee senna as hosts of common plant nematodes in Florida

Abstract: Yellow (Cyperus esculentus) and purple (C. rotundus) nutsedges, and coffee senna (Senna occidentalis) are common weeds in the southern USA and each have been reported as alternative hosts for plant-parasitic nematodes. Our objective was to determine the host suitability of these weeds to plant-parasitic nematodes common in Florida agriculture and turfgrass systems. The root-knot nematode (RKN) species tested included Meloidogyne arenaria, M. enterolobii, M. floridensis, M. graminis, M. hapla, M. incognita, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…Kaur et al (2007) found sicklepod to be a good host for M. enterolobii , whereas our research determined sicklepod was a poor host. Belle et al (2017) found purple nutsedge to be resistant to M. incognita , and Mendes et al (2020) concluded that both yellow and purple nutsedge are susceptible to M. enterolobii and M. incognita , while the present work determined purple nutsedge to be susceptible to M. incognita but resistant to M. enterolobii ( Table 1 ).…”
Section: Discussionsupporting
confidence: 44%
“…Kaur et al (2007) found sicklepod to be a good host for M. enterolobii , whereas our research determined sicklepod was a poor host. Belle et al (2017) found purple nutsedge to be resistant to M. incognita , and Mendes et al (2020) concluded that both yellow and purple nutsedge are susceptible to M. enterolobii and M. incognita , while the present work determined purple nutsedge to be susceptible to M. incognita but resistant to M. enterolobii ( Table 1 ).…”
Section: Discussionsupporting
confidence: 44%